Recent Advances of Tannase: Production, Characterization, Purification, and Application in the Tea Industry - Zhanhui Tang; Liyu Shi; Shuang Liang; Junfeng Yin; Wenjiang Dong; Chun Zou; Yongquan Xu (Foods)
Tannase, as a type of tannin−degrading enzyme, can catalyze the hydrolysis of ester and depside bonds in gallotannins, thereby releasing gallic acid and glucose. Based on this reaction mechanism, Tannase can effectively improve the problems of bitter taste, weak aroma, and tea cheese in tea infusion, and is therefore widely used in the tea industry. However, due to high production costs, difficulties in purification and recovery, and insufficient understanding of Tannase properties, the large−scale application of Tannase is severely limited. Therefore, the sources of Tannase and the effects of fermentation temperature, pH, stirring speed, time, carbon, and nitrogen sources on the preparation of Tannase are described in this study. The advantages and disadvantages of various methods for measuring Tannase activity and their enzymatic characterization are summarized, and the concentration and purification methods of Tannase are emphasized. Finally, the application of Tannase to reduce the formation of tea precipitate, enhance antioxidant capacity, increase the extraction rate of active ingredients, and improve the flavor of the tea infusion is described. This study systematically reviews the production, characterization, purification, and application of Tannase to provide a reference for further research and application of Tannase.